Osteoarthritis Medication and Overview: A Narrative Review - Partan, Radiyati Umi (HM Publisher, 2022)
Osteoarthritis, the most common form of joint disease, is primarily a disease of aging. Ninety percent of all people have radiographic features of osteoarthritis in weight-bearing joints by age 40. Symptomatic disease increases with age. Risk factors for this disorder include gender, genetics, obesity, and work history. Osteoarthritis develops in women more often than in men. This arthropathy is characterized by cartilage degeneration and bony hypertrophy at the articular margins. Inflammation is usually minimal. Hereditary and mechanical factors may be involved in the pathogenesis. This review provides an overview of counseling osteoarthritis and its treatment and management.